(untitled) (Sains Humanika, 2014)
The properties are among the five important things that need to be preserved in the Islamic Shari’ah using financial management mechanisms to meet the fair and clear principles of maqasid Shari’ah (Shari’ah Objectives). Although many researchs have been done in this area but, this article focuses on five main themes. That is, the maqasid Shari’ah and its importance in financial management. Next, the relationship between maqashid Shari’ah and ijtihad in financial management. Furthermore, maqashid Syaria’ah and insurance nomination. Finally, analysis the elements of magashid Shari’ah in fatwa on insurance nomination. Although the study represents these themes, the study focused on Singapores’ fatwa on the issue of succession in the insurance nomination and its integration with the maqashid theory as a wayÂ out to new problems of society.Â Â